(untitled) (Revista Contexto & Saúde, 2023)
The prescription and use of psychotropic drugs in primary health care have been increasing over the years. The present study aimed to analyze the use of psychotropic drugs in two Basic Health Units located in Ceilândia-DF. A retrospective documentary research was conducted, analyzing the dispensation records of two Health center contained in the BI-Horus (Bussiness Intelligence) database from the year 2019 and 2020.The results show a 45% increase in the prescription of psychotropic drugs in Basic Health Unit 6 of Ceilândia and a 17% decrease in Basic Health Unit 8. Most users of psychotropic drugs are adults between 18 and 59 years old with a prevalence of female gender. The most dispensed psychotropic drugs were fluoxetine, amitriptyline and carbamazepine respectively. Valproic acid 500mg accounted for over 25% of the total expenditure on psychotropic drugs in both units. Most of the prescriptions seen were not made by Neurologists or Psychiatrists. We emphasize the importance of pharmacoepidemiology, especially the Studies on the Use of Medications (EUM), since through this knowledge it is possible to organize preventive actions and the rational use of psychotropic drugs.